A Conceptual Framework to design Users Digital Legacy Management Systems - Pereira, Fabrício Horácio Sales Pereira; Prates, Raquel Oliveira Prates (Teste, 2018)
Current computer systems facilitate interaction between users for various purposes, including the management of their Digital Legacy. The Digital Legacy of a user is formed by several items and virtual possessions that have some type of value (e.g., financial, affective or of another nature) to someone, for the individual himself/herslef or other stakeholders. Systems that aim to support the management of users' digital legacy cover a series of configurations with long-term effects, as well as implementing different ways of handling temporality of information and organizing the roles users can take. In this paper, we propose a conceptual framework to support the designers of Digital Legacy Management Systems (DLMS), by describing the dimensions that are relevant to these systems and the values they can take. The framework was proposed based on a systematic analysis of 6 Digital Legacy Management Systems, using the Semiotic Inspection Method in combination with the Interaction Anticipation Design Challenges. The preliminary evaluation of our framework yielded initial positive indicators about its use in the design of a DLMS prototype.